A smart card-based access control system for the Department of Computer Science Library - Leona, Mark Jesus C.
A typical library system had provisions for defining users and user access requests. These access requests included borrowing and returning of library materials. Such requests were granted or disallowed based on a defined access control policy. We proposed to design and implement a smart card-based access control system for a typical library. Our intent was to take advantage of the high processing power and limited storage capabilities of a smart card to provide additional services for library users. We investigated the incorporation of an electronic purse to enable payment for certain fee-based requests. We also investigated the use of low footprint databases to allow for some offline transactions. Our initial target was to apply these solutions to the University of the Philippines Diliman Department of Computer Science Library.